Analisis Dan Perancangan Sistem Informasi Penjualan Rumah Berbasis Web Pada PT Indah Cemani Raya Balaraja - Imam Aji Santoso; Ria Agustina; Fauziah Nur Akmalia (UNIVERSITAS RAHARJA, 2021)
The system used by the company in handling the recording and sale of home products is still done manually as to hamper the company's performance. In a sense, a company is a unified system that influences one another to achieve certain goals. In the proposed system that the author designed to solve these problems while providing information on home sales quickly. For example, data processing needs are increasing, data processing rules are increasingly varied, rules from within or outside the company, can be used as indicators of problems. So PT Indah Cemani Raya, Balaraja designed the application for a web-based balaraja housing information system. This system is used to facilitate the process of sales, promotions and detailed information about balaraja housing, where marketing can enter home listings entrusted by customers to the website of PT Indah Cemani Raya, Balaraja to be marketed, and the existence of an application to activate the list of home sales that have been inputted by marketing to the website. Reports produced are in the form of home data reports, home buyer reports, home marketing reports, periodic payment reports, house specifications and credit simulations. Currently there is no system to facilitate customers in seeing housing products and also place an order without having to come to the location. The purpose of writing this journal is to analyze and design a sales system at PT Indah Cemani Raya, Balaraja so that it can help the parties involved in the data collection process, especially in the home sales process. PT Indah Cemani Raya, Balaraja is a private company engaged in the property business, specifically in the sale of housing construction (developers) which helps the government in increasing national economic development.